Enhanced photon collection enables four dimensional fluorescence nanoscopy of living systems - Luciano A. Masullo (Nature Portfolio, 2018)
Super-resolution microscopy often suffers from low contrast and slow recording times. Here the authors present an optical implementation which makes the fluorescent proteins’ ON–OFF switching cycles more efficient, enhancing contrast and spatio-temporal resolution in 3D cell and tissue imaging.